Vitamin D in Graves Disease: Levels, Correlation with Laboratory and Clinical Parameters, and Genetics - Planck, Tereza (Eur Thyroid J, 2018)
OBJECTIVE: The aim was to compare the vitamin D levels in patients with Graves disease (GD) with the general population and to correlate the vitamin D levels with laboratory and clinical parameters in GD. Moreover, we examined the genetic variation in genes involved in the vitamin D metabolism and their association with GD. METHODS: The levels of vitamin D were compared in 292 patients with newly diagnosed GD and 2,305 controls. Single nucleotide polymorphisms (SNPs) in the vitamin D receptor (VDR), vitamin D binding protein (DBP), and 1-α-hydroxylase (CYP27B1) were examined for association with GD and/or Graves ophthalmopathy (GO) in 708 patients and 1,178 controls. RESULTS: Patients with GD had significantly lower vitamin D levels compared to controls (55.0 ± 23.2 vs. 87.2 ± 27.6 nmol/L, p < 0.001). In patients with GD (n = 219), there was no association between the levels of vitamin D at diagnosis and free thyroxine (fT(4)), free triiodothyronine (fT(3)), thyrotropin receptor antibodies (TRAb), GO at diagnosis, or relapse after terminating treatment with antithyroid drugs. Two SNPs in VDR were associated with GD: rs10735810 (OR = 1.36, 95% CI: 1.02–1.36, p = 0.02) and rs1544410 (OR = 1.47, 95% CI: 1.03–1.47, p = 0.02). There was no difference in the mean vitamin D level between genotypes in either rs10735810 or rs154410. CONCLUSIONS: Patients with GD had lower vitamin D levels compared to the general population; however, the vitamin D levels did not affect the laboratory or clinical parameters of GD. SNPs in the VDR influenced the risk of GD through mechanisms other than reducing the vitamin D levels.